2020
DOI: 10.1002/hbm.25178
|View full text |Cite
|
Sign up to set email alerts
|

Resting theta activity is associated with specific coding levels in event‐related theta activity during conflict monitoring

Abstract: Brain electrical activity in the theta frequency band is essential for cognitive control (e.g., during conflict monitoring), but is also evident in the resting state. The link between resting state theta activity and its relevance for theta-related neural mechanisms during cognitive control is still undetermined. Yet, theoretical considerations suggest that there may be a connection. To examine the link between resting state theta activity and conflict-related theta activity, we combined temporal EEG signal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…EEG theta oscillations during cognitive control tasks may reflect input integration processes that lead to the detection of the need for cognitive control 15 , 34 . This may be possible because cognitive control-related EEG theta activity originates in cortical layers 2 and 3 14 , 15 , which yield a cellular architecture ideally suited to filter, amplify and integrate information 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EEG theta oscillations during cognitive control tasks may reflect input integration processes that lead to the detection of the need for cognitive control 15 , 34 . This may be possible because cognitive control-related EEG theta activity originates in cortical layers 2 and 3 14 , 15 , which yield a cellular architecture ideally suited to filter, amplify and integrate information 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…To measure the participants’ resting theta activity, we used the same setup as reported in previous studies 21 , 34 . We asked the participants to relax for two minutes with their eyes open while looking at a computer screen.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the Go/Nogo task does not allow to disentangle whether the increased theta activity during Nogo trials is related to the alarm/surprise signal or to inhibitory control per se. However, recent findings on a different aspect of cognitive control (i.e., conflict monitoring) have shown that resting theta activity is specifically related to stimulus‐related, but not to response‐related processes (Pscherer et al, 2020 ), which supports the concept that theta activity acts as alarm/surprise signal or facilitates the processing of such signals.…”
Section: Discussionmentioning
confidence: 74%
“…The participants' resting theta activity was assessed using the same setup as reported in a previous study (Bluschke, Broschwitz, Kohl, Roessner, & Beste, 2016 ; Pscherer et al, 2019 ; Pscherer et al, 2020 ), based on the same electronic devices and the same data recording system (BrainVision Recorder by Brain Products Inc.) as the setup for assessing the task‐related EEG (see Section 2.5 ). For this purpose, subjects were asked to relax with their eyes open for a 2‐min time interval while focusing on a PC screen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation